Energizing everyday practices through the indigenous spirituality of haka. Issue 1 (2nd January 2017) - Smith, Valance
ABSTRACT: For many Māori, the dominant Western episteme of materialism and individualism does not underpin a Māori way of intimately connecting to and knowing the land and contemporary Aotearoa New Zealand society. Occupational science can profit from the insights that Māori spirituality is nonetheless, spirituality and, in its divinity, can transcend and talk meaningfully to all cultures and peoples who choose to engage. In this paper, I investigate how Māori spirituality can inspire everyday practices through the medium of haka – Māori performance art. I investigate the nature of indigenous Māori spirituality and its relationship to art, proposing that Māori spirituality is a cultural framework that inspires, energizes, and synergizes all those who engage and share in its life force. I seek to create systematic foundations for everyday occupations based on kaupapa (goal, purpose), mārama (enlightenment, understanding), pono (truth, integrity), tika (right and correct conduct), aroha (love, passion), and mana (power, wisdom); concepts deeply rooted in Māori culture and history. Each concept is linked to form a foundational framework, with the performance art of haka being a medium to mobilize this framework, and in turn spiritually energize people's everyday occupations.